Preparation and Characterizations of Zeolite – Filled Natural Rubber/Poly(vinyl alcohol) Semi–IPN Membranes - Patthana, J.; Poonsawat, C.; Amnuaypanich, S. (Journal of Applied Membrane Science & Technology, 2017)
Semi–interpenetrating polymer network (semi–IPN) of natural rubber (NR) and crosslinked poly(vinyl alcohol) (PVA) was composited with zeolite 4A to form a mixed matrix (MM) membrane. PVA was crosslinked with sulfosuccinic acid (SSA) in the immediate presence of NR and zeolite. FT–IR spectroscopy confirmed the crosslinking of PVA in the MM membrane. Swelling measurements were carried out in both water and absolute ethanol. The degrees of swelling in both water and ethanol increased with increasing PVA content in the membranes, however they were found to decline upon increasing zeolite content more than 10 %w/w. The mechanical properties of the MM membranes were investigated by tensile testing. It was observed that the modulus increased with increasing zeolite content in membranes but the elongation at break was found to decrease. The thermal degradation of the MM membranes was studies using thermal gravimetry (TG). The MM membranes showed higher thermal stability compared with NR/PVA membrane due to the incorporation of zeolite. The dispersion of zeolite particles in the MM membrane was observed by scanning electron microscopy (SEM) analysis which showed a well dispersing of zeolite particles in the semi–IPN matrix. The sorption selectivities of MM membranes were enhanced with zeolite content especially, at low water concentration of ethanol–water mixtures. However the sorption selectivities of MM membranes decreased when water content in the liquid mixtures increased.